Education in China: Challenges and Prospects of the 21th Century - Nalyvaiko, Oleksii; Nalyvaiko, Natalііa (Educological discourse, 2024)
The study is dedicated to a detailed analysis of the modern education system in the People’s Republic of China (PRC), focusing on its historical development, key reforms, as well as the challenges and prospects the country faces in the context of globalization and digitalization. The main idea of the article is that education in China is a crucial component of national development, closely linked to the country’s economic and social transformations. The authors emphasize the significance of the educational reforms implemented in the 21st century, particularly the introduction of a new curriculum that shifts the focus from traditional rote learning to the development of critical thinking, creativity, and practical skills. The article addresses the key challenges facing China’s education system: socio-economic inequality between urban and rural areas, high levels of stress among students due to the rigorous examination system, and insufficient teacher training, especially in rural areas. The authors note that, despite significant achievements, these issues remain relevant and require further attention and resolution. The research highlights that China is actively working to overcome these challenges through various reforms, including the "double reduction" policy, which aims to reduce the academic burden on students and improve their well-being. The importance of developing vocational education, which better aligns the education system with the needs of the labor market, is also emphasized. In conclusion, the article underscores that the future of education in the PRC will be shaped by further informatization, internationalization, and continued reforms aimed at enhancing educational equity and quality. International cooperation, which facilitates the exchange of experiences and the implementation of best practices in the Chinese education system, plays a crucial role in this process. Overall, the Chinese experience can be valuable for other countries seeking to improve their education systems in the context of global transformations.